A survey of the flora and fauna of Pulau Punyit, Brunei Darussalam. - Das, Indraneil; Booth, W. E.; Wong, K. M.; Kamariah, A. S.; Choy, S. (Forest Research Centre, Sabah, 1997)
Pulau Punyit supports only 20 species of terrestrial plants, a feature reflecting the small size of this island and its harsh environment. The species include 3 ferns, 3 monocotyledons (including Cocos nucifera), and 14 dicotyledons (10 trees and 4 climbers). The most common tree species are Excoecaria agallocha, Allophylus cobbe and Diospyros maritima. Of the other species, Gastonia serratifolia (a tree), is known in Brunei from this island only, and Melientha suavis subsp. suavis (a [woody] climber) is a new subspecies record for Borneo. The herpetofauna is limited to one snake and one lizard. The littoral zone, in contrast, supports a wide variety of algae and invertebrates, many of which are arranged in distinct patterns of zonation. Pulau Punyit, as one of only two offshore islands, represents a substantial proportion of the open coast and hard-substrate littoral biodiversity of Brunei Darussalam, and as such, should be protected.